2017
DOI: 10.1097/tp.0000000000001129
|View full text |Cite
|
Sign up to set email alerts
|

High Intrapatient Tacrolimus Variability Is Associated With Worse Outcomes in Renal Transplantation Using a Low-Dose Tacrolimus Immunosuppressive Regime

Abstract: This suggests that highly variable tacrolimus levels predict worse outcomes postrenal transplantation, although the causal nature of this relationship remains unclear. High tacrolimus variability may identify a subset of patients who warrant increased surveillance and patient education regarding dietary and medication compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
109
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(121 citation statements)
references
References 20 publications
5
109
3
4
Order By: Relevance
“…However, only 18 patients were nonwhite. 16 Based on the country of origin these studies were conducted, there were likely few if any patients of African descent in these analyses. There are several other studies also demonstrating that high tacrolimus variability, measured either by standard deviation or %CV, increases the risk of acute rejection and poor graft outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only 18 patients were nonwhite. 16 Based on the country of origin these studies were conducted, there were likely few if any patients of African descent in these analyses. There are several other studies also demonstrating that high tacrolimus variability, measured either by standard deviation or %CV, increases the risk of acute rejection and poor graft outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation was that tacrolimus concentrations obtained during hospitalization were also included in this analysis and we used a 10-year cohort and the study time period was long in relation to other studies. 1316 While this increased the sample-size, follow-up time and power of the analysis, it also meant that clinical care changed during the study period. This includes measurement of risk factors, including PRA, and donor marginality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High intra‐patient variability in calcineurin inhibitors (CNI) can worsen graft outcome and lead to rejection and Donor Specific Antibody (DSA) development . Although non‐adherence to the immunosuppressive drug regimen seems to be the main reason for a high variability in drug blood levels , relationships between non‐adherence patterns and drug exposure have not been systematically characterized in the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Risk of the composite outcome was 1.4 times higher in patients with high IPV, even after adjustment for confounders. The findings are not necessarily novel; a number of previous studies have demonstrated association between IPV and adverse outcomes in both adult and paediatric recipients, and in different solid organ transplant types . This study does, however, represent the largest series to date and includes a number of additional risk factors for poor transplant outcomes in multivariate analysis.…”
mentioning
confidence: 77%